Development of ACLS Electrodes for a Water Electrolysis Cell. (3rd July 2019) - Yoshinaga, Norihiro; Kanai, Yuta; Fukazawa, Taishi; Nakano, Yoshihiko; Mei, Wu
Abstract : An iridium electrocatalyst powder with a platinum-coated porous titanium layer is conventionally used as the anode in polymer electrolyte membrane (PEM) electrolyzers. However, these noble metals are scarce and expensive. To reduce their use, we developed an alternating catalyst layer structure (ACLS) consisting of multiple sputter-deposited iridium sheets and air-gap layers without a platinum coating layer. The ACLS electrocatalyst exhibited lower overvoltage at low iridium loading compared with a powder catalyst, and there was almost no voltage rise during 7, 000 h of operation. The ACLS is effective for reducing the amount of noble metals used in PEM electrolyzers.